Where does a Staphylococcus aureus vaccine stand?. (May 2014) - Fowler, V. G.; Proctor, R. A.
Abstract: In this review, we examine the current status of Staphylococcus aureus vaccine development and the prospects for future vaccines. Examination of the clinical trials to date show that murine models have not predicted success in humans for active or passive immunization. A key factor in the failure to develop a vaccine to prevent S. aureus infections comes from our relatively limited knowledge of human protective immunity. More recent reports on the elements of the human immune response to staphylococci are analysed. In addition, there is some controversy concerning the role of antibodies for protecting humans, and these data are reviewed. From a review of the current state of understanding of staphylococcal immunity, a working model is proposed. Some new work has provided some initial candidate biomarker(s) to predict outcomes of invasive infections and to predict the efficacy of antibiotic therapy in humans. We conclude by looking to the future through the perspective of lessons gleaned from the clinical vaccine trials.